The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13081993
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Instant Estimation of the Temperature Experienced by Fire-Damaged Reinforced Concrete Structures Using Titanium

Abstract: When a concrete structure is exposed to fire, its structural safety is significantly compromised due to the spalling of members and scaling of concrete. In addition, its durability is substantially reduced due to certain chemical changes such as the dehydration of Ca(OH)2, the main hydration product of concrete, and the rehydration of CaO. Therefore, when fire damage occurs to a reinforced concrete (RC) building, rapid diagnosis and evaluation techniques are required for immediate repair and reinforcement, req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Consequently, this mixture change, even in the hydrogen-balanced condition, impacts the rate of axial growth. While the growth rate decreases, the fiber-to-fiber growth rate variation did reduce, albeit a modest decrease in Titanium oxide is known to exhibit a bronze color at low temperatures and a white color at higher temperatures [34]. The hydrogen-balanced (1:1) fibers exhibited a varying temperature gradient as it deposited, which was visible in Figure 7a, and where such thermal gradients would have created convective motion of the gases around the fiber that would lead to the oxidization of titanium.…”
Section: Resultsmentioning
confidence: 98%
“…Consequently, this mixture change, even in the hydrogen-balanced condition, impacts the rate of axial growth. While the growth rate decreases, the fiber-to-fiber growth rate variation did reduce, albeit a modest decrease in Titanium oxide is known to exhibit a bronze color at low temperatures and a white color at higher temperatures [34]. The hydrogen-balanced (1:1) fibers exhibited a varying temperature gradient as it deposited, which was visible in Figure 7a, and where such thermal gradients would have created convective motion of the gases around the fiber that would lead to the oxidization of titanium.…”
Section: Resultsmentioning
confidence: 98%
“…We set the time for plasma application to 30 s, which seems appropriate for the chair side of clinical dental treatment. Ti shows discoloration owing to the formation of an oxide film on the surface at high temperature [ 35 ], which suggests that a handheld plasma device is a useful tool for adding hydrophilization on Ti disks without discoloration. Our results showed that the handheld plasma device had no effect on the roughness of the Ti surface.…”
Section: Discussionmentioning
confidence: 99%
“…The compressive strength of concrete can decrease by up to 50 percent if the concrete is exposed to 600 °C. When concrete is exposed to fire for a long period, the concrete strength is reduced [2,3]. Also, the reinforcement steel strength inside the concrete was reduced [4].…”
Section: Introductionmentioning
confidence: 99%